2011
DOI: 10.4317/medoral.16.e124
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the nuclear factor kappa-beta (NF-kB) in cortical of mice Wistar using Technovit 7200 VCR

Abstract: Objective: this study aimed to develop a nondecalcified bone sample processing technique enabling immunohistochemical labeling of proteins by kappa-beta nuclear factor (NF-kB) utilizing the Technovit 7200 VCR ® in adult male Wistar rats. Study Method: A 1.8 mm diameter defect was performed 0.5mm from the femur proximal joint by means of a round bur. Experimental groups were divided according to fixing solution prior to histologic processing: Group 1-ethanol 70%; Group 2-10% buffered formalin; and Group 3-Glyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…For these samples, as against staining, Mayers' hematoxylin (EnVision tm Flex, Dako), was used. The analysis was performed, under standard light microscopy (Salles et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…For these samples, as against staining, Mayers' hematoxylin (EnVision tm Flex, Dako), was used. The analysis was performed, under standard light microscopy (Salles et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Sixty-five Wistar male rats weighing ~350 g were divided into 13 groups ( n = 5 per group). The eight experimental groups (expG 1–8) were divided in accordance with the euthanasia time: zero, 1 h, 2 h, 4 h, 6 h, 8 h, 12 h, and 24 h; the five control groups sham (conG 1–5) or false-operated groups were killed at zero, 1 h, 2h, 4 h, and 6 h. The sham group was performed only in these 5 times, because in a previous study performed and published to evaluate the technique used was found in the other time there was no mark [ 20 ], decreasing the number of animals used.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were immersed in a fixative solution of 10% buffered formalin (0.1 molar phosphate buffer, pH 7.4), at 4°C for 7 days [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations